Use of aortic wall patches as leaflet replacement material during aortic valve repairCentral MessagePerspective - John L. Myers, MD; J. Brian Clark, MD; Timothy W. James, MD; Emily Downs, MD; Saad M. Hasan, MD; Robert S. Binford, MD; Jeffrey D. McNeil, MD; Victor M. Rodriquez, MD; Christopher E. Mascio, MD; Lawrence M. Wei, MD; Vinay Badhwar, MD; J. Scott Rankin, MD (JTCVS Techniques)
Objectives: Aortic valve repair can be limited by inadequate leaflet tissue for proper coaptation. Various kinds of pericardium have been used for cusp augmentation, but most have failed because of tissue degeneration. A more durable leaflet substitute is needed. Methods: In this report, 8 consecutive cases are presented in which autologous ascending aortic tissue was used to augment inadequate native cusps during aortic valve repair. Biologically, aortic wall is a living autologous tissue that could have exceptional durability as a leaflet substitute. Techniques for insertion are described in detail, along with procedural videos. Results: Early surgical outcomes were excellent, with no operative mortalities or complications, and all valves were competent with low valve gradients. Patient follow-up and echocardiograms to a maximum of 8 months’ postrepair remain excellent. Conclusions: Because of superior biologic characteristics, aortic wall has the potential to provide a better leaflet substitute during aortic valve repair and to expand patient categories amenable to autologous reconstruction. More experience and follow-up should be generated.